PENINGKATAN HASIL BELAJAR MATEMATIKA SISWA PADA POLINOMIAL MELALUI DISCOVERY LEARNING - Nuha Dila, Aulia; Harun, Zulkardi (JURNAL e-DuMath, 2019)
This research was conducted in class XI MIPA 4 SMA Negeri 1 Palembang totaling 36 students in polynomial material carried out in two cycles. Data collection techniques used in this study were tests and observations, with instruments in the form of test questions and observation sheets. Based on the result of the analysis it was concluded that mathematics learning in polynomial material through Discovery Learning can improve the mathematics learning outcomes of students of class XI MIPA 4 SMA Negeri 1 Palembang on the material. In the first cycle students who had completed were 55.55% with an average of 75.69. Then in the second cycle, students who have completed increased to 69.44% with an average of 80.58.